Gastrointestinal Diseases in Pregnant Women: A Retrospective Analysis - Dugad, Ayush Sharadchand; Sunny, Kumar; Bharadwaj, Kavuloori Sai Rithish; Aringazina, Raisa A. (Journal of Infertility and Reproductive Biology, 2025)
This study presents the findings from a study investigating the prevalence of specific gastrointestinal (GI) tract pathologies in pregnant women and their association with neonatal outcomes during the early neonatal period. The investigation is motivated by the high frequency of GI comorbidity during gestation and its potential to adversely affect neonatal status. The pathophysiological mechanisms underlying these conditions, occurring within the context of physiological adaptations to pregnancy, are delineated. Analysis of the clinical data identified chronic gastritis (36.3%), chronic cholecystitis (23.3%), and hepatobiliary diseases (24.2%) as the most prevalent diagnoses among the studied cohort of pregnant women. Neonatal assessment via the APGAR score revealed that infants born to mothers with hepatobiliary diseases had the lowest mean score at one minute (7.2 ± 0.7), compared to 7.8 ± 0.4 for those born to mothers with chronic gastritis. By the fifth minute of life, APGAR scores improved across all groups, ranging from 8.2 ± 0.6 to 8.7 ± 0.3 points. The findings indicate that maternal somatic pathology, particularly chronic GI disease, constitutes a significant risk factor for compromised early postnatal adaptation. Consequently, the timely diagnosis of these conditions in pregnancy and the active correction of associated metabolic disturbances are imperative clinical objectives for improving perinatal outcomes.